Dampak Teknik Akuntansi Kreatif dan Pajak Kreatif Terhadap Keandalan Laporan Keuangan Dengan Religiusitas Sebagai Variabel Moderasi (Studi Kasus: Akuntan di Kota Semarang) - Warno Warno; Fiderika Dewi Widyasari; Ali Murtadho (Indonesian Accounting Literacy Journal, 2021)
Abstract: This research is motivated by the number of managers who deliberately manipulate the company's financial statements to attract stakeholder interest and goals related to competition. This study aims to determine the effect of creative accounting and creative tax on the depth of financial statements with religiosity as a moderating variable. The objects in this study are accountants in companies located in the Wijaya Kusuma Industrial Estate, Semarang. The type of research used is quantitative research. Data was collected by distributing questionnaires presented on a Likert scale. Sampling in this study was conducted by purposive sampling obtained 34 respondents in 11 companies. The results showed that creative accounting and creative tax variables had a significant negative effect on the reliability of financial statements. And the religiosity variable moderates the creative accounting and creative tax variables on the reliability of financial statements. Keywords: Financial Report Reliability, Creative Accounting, Creative Tax, Religiosity Financial Report Reliability, Creative Accounting, Creative Tax, Religiosity